PRE-FRONTAL CORTEX NEUROMODULATION BY RTMS AND NEUROFUNCTIONAL TRAINING IN CHILDREN WITH AUTISM SPECTRUM DISORDER: A RANDOMIZED, DOUBLE-BLIND, CONTROLLED CLINICAL TRIAL (CIPEEX, 2025)
The objective of this study is to compare the functional effects of ten sessions of neurofunctional training associated with repetitive transcranial magnetic stimulation (rTMS) on the active left dorsolateral prefrontal cortex and placebo in children with ASD.  This is a randomized, placebo-controlled, double-blind clinical trial involving 24 children diagnosed with ASD, aged between three and eight years. The children will be randomly assigned to two groups: Experimental group – neurofunctional training and active rTMS; and Control group – neurofunctional training and placebo rTMS. Participants will be assessed one week before the intervention, one week and one month after the end of the interventions, using the Childhood Autism Rating Scale, Autism Classification System: Social Communication, timed up and go, 10-meter walk test, Pediatric Balance Scale, and Participation and Environment Measure - Children and Youth. The interventions will consist of five sessions per week, carried out over two consecutive weeks. rTMS will be applied to the left dorsolateral prefrontal cortex for 20 minutes at a high frequency (5Hz). After rTMS application, participants will undergo neurofunctional training for 20 minutes. Neurofunctional training will consist of a circuit of activities (10 minutes) and gait training on a treadmill (10 minutes). The results will be analyzed statistically assuming a significance level of p≤0.05.
Keywords: autism spectrum disorder; gait; balance; child; physical therapy; transcranial magnetic stimulation